Subtract ( 3g - 4 ) + 2 ( 3g + 4 )

1 answer

To subtract the expression \((3g - 4) + 2(3g + 4)\), we'll follow these steps:

  1. Distribute the 2 in the second term: \[ 2(3g + 4) = 2 \cdot 3g + 2 \cdot 4 = 6g + 8 \]

  2. Combine the two parts of the expression: \[ (3g - 4) + (6g + 8) \]

  3. Combine like terms:

    • Combine the \(g\) terms: \(3g + 6g = 9g\)
    • Combine the constant terms: \(-4 + 8 = 4\)

    So, we have: \[ 9g + 4 \]

The final answer for the expression \((3g - 4) + 2(3g + 4)\) is: \[ 9g + 4 \]